A tagging polymorphism in fat mass and obesity-associated (FTO) gene is associated with sepsis status in children - Jabandziev, Petr; Hubacek, Jaroslav Alois; Michalek, Jaroslav; Jouza, Martin; Papez, Jan; Pecl, Jakub; Slaba, Katerina; Slaby, Ondrej; Urik, Milan; Aulicka, Stefania; Kunovsky, Lumir; Michalek, Jaroslav; et al. (Revue roumaine de médecine interne, 2024)
INTRODUCTION: Sepsis is one of the most common causes of death in patients admitted to intensive care units (ICUs). The development of sepsis is significantly influenced by genetic predisposition. In this study, we highlight a potential association between a variant of the fat mass and obesity-associated (FTO) gene and risk of sepsis in children and adolescents. METHODS: We investigated a first-intron tagging FTO polymorphism (rs17817449) by comparing a severe condition (SC) group, comprising 598 paediatric patients (ages 0-19 years) admitted to an ICU with fever, systemic inflammatory response syndrome (SIRS), sepsis, severe sepsis, septic shock, or multiple organ dysfunction syndrome (MODS), with a control group consisting of 616 healthy young adults. RESULTS: We observed a lower prevalence (p < 0.01; OR = 0.59, 95% CI = 0.39-0.87) of the FTO TT genotype in febrile and SIRS patients compared to patients with severe illness. There was a borderline trend towards a lower prevalence of the FTO TT genotype in the control group compared to the SC group (p < 0.09, OR = 0.81, 95% CI = 0.62-1.06). CONCLUSIONS: Our findings suggest that rs17817449, a common FTO polymorphism, may be a predictor of sepsis in paediatric patients, and that higher body weight is protective against this clinical complication.
Keywords: Young Adult; gen pro FTO; Male; Systemic Inflammatory Response Syndrome; multiorgánové selhání; Child, Preschool; Genetic Predisposition to Disease; Genotype; mladý dospělý; polymorfismus genetický; Adolescent; Infant; sepse; Child; dítě; Case-Control Studies; mužské pohlaví; jednonukleotidový polymorfismus; Multiple Organ Failure; Polymorphism, Genetic; mladiství; Sepsis; novorozenec; předškolní dítě; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; studie případů a kontrol; syndrom systémové zánětlivé reakce; Humans; Infant, Newborn; kojenec; genotyp; Female; genetická predispozice k nemoci